Coupled stretching–bending analysis of laminated plates with corners via boundary elements. (February 2015) - Hwu, Chyanbin; Chang, H.W.
Abstract: To cover all the possibility of symmetric, anti-symmetric, or unsymmetric thin laminated plates, the fundamental solutions used in the present boundary element was obtained from the Green's functions for the coupled stretching–bending analysis. Considering the possible existence of corners in thin laminated plates, four different approaches were proposed and compared to deal with the corners: (1) round-off corners, (2) triple independent nodes on the boundary, (3) triple independent nodes outside the boundary, and (4) triple nodes with the same position on the corner. Due to the equation dependency raised by the same position of the fourth approach, four auxiliary equations suited for various boundary conditions were derived by considering the symmetry of stress tensor and using the laminate constitutive relations. The numerical results show that the last two approaches perform well in all examples, whereas the first two fail in certain cases of the unsymmetric laminates.